Marketing Strategy to Improve Export Services of PT. Varuna Tirta Prakasya (Persero) in National Market Competition - Rezki Ardiansyah; Isna Wijayani (Institute of Computer Science (IOCS), 2022)
PT. Varuna Tirta Prakasya (Persero) is one of the SOEs engaged in logistics and is experienced and trusted, where this company serves export and import services. In the process of improving the Indonesian economy, one thing that needs to be considered is the increase in state income. For this reason, state revenues are related to the export process carried out by PT. Varuna Tirta Prakasya (Persero). However, in the national market competition, the marketing process of PT. Varuna Tirta Prakasya (Persero) has not been so good. Therefore, in this study, we analyzed and recommended suitable marketing strategies so that PT. Varuna Tira Prakasya (Persero) can compete in the national market and can help increase state income through exports.